2015
DOI: 10.1111/bju.13354
|View full text |Cite
|
Sign up to set email alerts
|

The impact of re‐transurethral resection on clinical outcomes in a large multicentre cohort of patients with T1 high‐grade/Grade 3 bladder cancer treated with bacille Calmette–Guérin

Abstract: Objectives To determine if a re-TUR in the presence or absence of muscle at the first TUR in T1-high grade (HG)/G3 bladder cancer patients makes a difference in recurrence, progression, cancer specific (CSS) and overall survival (OS). Methods In a large retrospective multi-centre cohort of 2451 T1-HG/G3 patients initially treated with BCG, 935 (38%) had a re-TUR. According to the presence or absence of muscle in the specimen of the primary TUR, patients were divided in 4 groups: group 1 (no muscle, no re-TUR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
99
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 19 publications
7
99
3
3
Order By: Relevance
“…These patients with unexpected residual disease would have risked progression while on BCG. Many studies have reported that around 50% of patients newly diagnosed with cT1 tumors presented with residual tumor at restaging TUR within 6 weeks after initial resection (Table 4) [820]. According to a meta-analysis conducted by Vianello et al, the residual rate at second TUR is 47% (95% CI = 0.41–0.53) [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients with unexpected residual disease would have risked progression while on BCG. Many studies have reported that around 50% of patients newly diagnosed with cT1 tumors presented with residual tumor at restaging TUR within 6 weeks after initial resection (Table 4) [820]. According to a meta-analysis conducted by Vianello et al, the residual rate at second TUR is 47% (95% CI = 0.41–0.53) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Female sex, age, tumor size, concomitant CIS and CIS in the prostatic urethra are important prognostic factors in T1 patients treated with BCG [25]. In a recently published international, multicentric, retrospective study, re-TUR in the presence of muscle in the primary specimen didn’t improve the outcomes, and re-TUR in the absence of muscle had a borderline significant positive impact on time to recurrence, time to progression, overall survival and cancer specific survival [20]. However, in a randomized study, patients with T1 disease at first TUR had a two-fold increased risk of recurrence and a four-fold increased risk of progression when re-TUR was not done [23].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Vasdev et al [23] found that 23.8% patients with T1G3 on TUR had residual T1 G3 on re-TUR. On the other hand, Gontero et al [15] reported even a higher rate (30.9%) in a multicenter international study. Recently, a prospective study that included 198 patients with T1 HG/G3 also showed that 1/4 of patients have T1 HG/G3 on re-TUR; they also demonstrated that extent of T1 invasion did not eliminate the need for re-TUR [24].…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, the presence of T1 on re-TUR after the initial TUR showing T1 HG/G3 confers worse survival in singlecenter or multicenter heterogeneous datasets. These studies are impacted by the negative effects of variable and sometimes older BCG therapy schemes among other design limitations [15,16]. Persistent disease after initial T1 HG/G3 BC is indeed in approximately 33-55% of patients [15][16][17], supporting the recommendation for re-TUR in all patients with T1 HG/G3 [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation